PENINGKATAN PEMAHAMAN KANDUNGAN AYAT AL-QUR’AN HADITS MELALUI STRATEGI PEMBELAJARAN KONTEKSTUAL PADA SISWA MTSN 1 BENGKULU UTARA - Novianti Hardini; Nurlaili; Dayun Riadi (STKIP Subang, 2026)
Learning of the Qur’an and Hadith at MTsN 1 North Bengkulu faces a fundamental challenge: students are expected to be able to read selected verses, understand the science of tajwid, and analyze the content of the verses. However, most students still experience difficulties in reading the Qur’an fluently. This gap in basic competencies hinders the achievement of learning objectives in a comprehensive manner. This study aims to: (1) describe the implementation of a CTL strategy adapted to address the heterogeneity of Qur’an reading abilities and (2) analyze its impact on improving students’ tajwid skills and understanding of verse content at MTsN 1 North Bengkulu. The method used was Classroom Action Research by applying a Contextual Teaching and Learning (CTL) strategy modified with a differentiated approach to address the heterogeneity of reading abilities among eighth-grade students. Data were collected through observation, reading ability tests (tilawah), tajwid comprehension tests, and evaluations of students’ understanding of verse content. The results of implementing CTL with reading-ability-based scaffolding showed positive outcomes. The percentage of students who were able to read verses with correct tajwid increased from 25% (pre-cycle) to 85% (Cycle II). Understanding of verse content also improved, with the average score increasing from 65 to 85%. Students with low reading abilities demonstrated significant progress through peer tutoring assistance and audio-visual media. It can be concluded that a contextual learning strategy adapted with a differentiated approach is effective in bridging gaps in basic Qur’an reading skills while simultaneously enhancing students’ understanding of tajwid and verse content.